The effects of altitude levels on 222Rn concentration in academic building at Universiti Malaysia Kelantan Jeli campus - Mohammad Khairul Azhar Abdul Razab; Siti Fatimah Abd Karim; Nur Ezati Azhar; Nur Liyana Hamzah; Nor Hakimin Abdullah; An'Amt bin Mohamed Noor; Mazlan Mohamed; Zulhisyam Abdul Kari @ Abdullah; Noraina Adam (Trans Tech Publications, 2017)
Highly continuous exposure to Radon (222Rn) concentrations can affects human health and causes lung cancer. This study aims to monitor 222Rn concentration at different altitude and to investigate the correlation of 222Rn concentration with several environmental factors which are temperature, humidity and pressure in indoor space. Lecture rooms known as BK 4 in the first floor and BK 8 in the third floor of academic building at Universiti Malaysia Kelantan (UMK) Jeli Campus were selected as the study areas. The total of 210 readings of indoor 222Rn concentrations data have been collected using Radon Sentinel Model 1030. From the observation, the average of 222Rn concentration in BK 4 and BK 8 range from 0.36 pCi/L to 0.73 pCi/L and 0.40 pCi/L to 0.93 pCi/L, respectively. 222Rn concentration of BK 8; situated 14.4 meter above the ground level is higher than BK 4 which is 4.8 meter from the ground level. Negative correlations were obtained between 222Rn concentrations over pressure, temperature and humidity at BK 4. Meanwhile, 222Rn concentrations at BK 8 have shown positive correlation over pressure and humidity, but negative correlation over temperature.